Outdoor Education dan Self Concept - Satria, Teguh; Nur, Lutfi (Prodi PGSD Penjas FPOK UPI, 2020)
The deviation of social behavior of elementary school students lately is very alarming, it requires preventive and curative efforts in handling it.The focus of this study would like to see the contribution of outdoor education activities to students' self concept in the primary school of the UPI Campus Tasikmalaya Campus, Indonesia. 32 students were selected as samples through purposive sampling technique. The experimental method was used in this study. Data obtained through self concept scale questionnaire. The results of the study mentioned Outdoor Education activities contributed to the development of self concept. This finding can be used as an alternative by physical education teachers in the context of innovation and learning variation. Further research can be carried out on the development of other affective aspects such as assertive behavior.Â AbstrakÂ Penyimpangan perilaku sosial siswa sekolah dasar akhir-akhir ini sangat memprihatinkan, diperlukan upaya preventif dan kuratif dalam menanganinya. Fokus penelitian ini ingin melihat kontribusi aktivitas outdoor education terhadap self concept siswa di sekolah dasar laboratorium percontohan UPI Kampus Tasikmalaya, Indonesia. Sebanyak 32 siswa dipilih menjadi sampel melalui teknik purposive sampling. Metode eksperimen digunakan dalam penelitian ini. Data diperoleh melalui kuesioner skala self concept. Hasil penelitian menyebutkan aktivitas Outdoor Education memberikan kontribusi terhadap pengembangan self concept. Temuan ini dapat dijadikan alternatif oleh para guru pendidikan jasmani dalam rangka inovasi dan variasi pembelajaran. Penelitian selanjutnya dapat dilakukan terhadap pengembangan aspek afektif lainnya seperti perilaku assertif.